Electrochemical and surface studies on chemically modified glucose derivatives as environmentally benign corrosion inhibitors - Haque J.; Srivastava V.; Chauhan D.S.; Quraishi M.A.; Madhan Kumar A.; Lgaz H. (My University, 2025)
Three glucose derivatives, namely Ethylenediamine-modified glucose, Tetramethylenediamine-modified glucose, and Hexamethylenediamine-modified glucose with three different carbon chain lengths were synthesized using environmentally benign and low-cost reactants at ambient temperature. The synthesized derivatives were evaluated as inhibitors for mild steel corrosion in 1 M HCl using electrochemical, surface analysis (XPS, AFM and contact angle), as well as computational (DFT) techniques. The obtained results suggest that the synthesized glucose derivatives significantly mitigate the corrosion of mild steel and show a rise in the inhibition efficiency with increasing inhibitor dosage. The inhibitor adsorption obeyed the Langmuir isotherm. The XPS analyses provided an elucidation on the interaction of the inhibitors with the steel substrate. The DFT studies showed that the protonated forms of the inhibitors act more prominently compared to the neutral form. The inhibitor HMG having the alkyl chain with six carbon atoms exhibited the highest inhibition performance of >95% at 22.71 × 10−5 mol L−1. © 2020 Elsevier B.V.